2009
DOI: 10.1002/jbm.a.32479
|View full text |Cite
|
Sign up to set email alerts
|

Polymer fibers as contact guidance to orient microvascularization in a 3D environment

Abstract: We describe an in vitro culture process that uses 100-microm diameter poly(ethylene terephthalate) monofilaments as contact guidance of human umbilical vein endothelial cells (HUVECs) to orient the development of microvessels in a 3D environment. Untreated fibers, distanced either by 0.05, 0.1, 0.15, or 0.2 mm were first covered with HUVECs and then sandwiched between two layers of fibrin gel containing HUVECs. After 2 and 4 days of culture, cell connections and microvessels were evaluated. Cell connections fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Moreover, in 100-μm microgrooves, it was frequently observed that cell branches connected with each other and formed networks. As such networks would subsequently lead to the formation of lumens in a vascularization process, the present finding that the formation of multicellular network was predominant in 100-μm microgrooves may suggest that 100-μm microgrooves were a preferred condition among the four types, which is consistent with the findings of previous studies [5,10]. Therefore, this agreement proves that the microgroove structure can be an alternative experimental model to polymer fibers in the study of microvascularization.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, in 100-μm microgrooves, it was frequently observed that cell branches connected with each other and formed networks. As such networks would subsequently lead to the formation of lumens in a vascularization process, the present finding that the formation of multicellular network was predominant in 100-μm microgrooves may suggest that 100-μm microgrooves were a preferred condition among the four types, which is consistent with the findings of previous studies [5,10]. Therefore, this agreement proves that the microgroove structure can be an alternative experimental model to polymer fibers in the study of microvascularization.…”
Section: Discussionsupporting
confidence: 92%
“…PET fibers which had been used as a geometrical guidance to endothelial cells for microvascularization in previous studies [5,10], were replaced with a micrometer-scale structure, microgrooves. Using MEMS techniques, microgrooves with different sizes (groove width) can be patterned in a small area.…”
Section: Experimental Modelmentioning
confidence: 99%
See 3 more Smart Citations